Editor's note - Sebolai, Kabelo (Journal for Language Teaching, 2023)
It is my pleasure to present the third publication of the Journal for Language Teaching since its move to Open Access at the beginning of 2022. The journal has continued to receive submissions focusing on a myriad of topics mainly on academic literacies and multilingualism in higher education in South Africa. This issue also includes an article wherein corpus tools were used to investigate the use of phrasal verbs by under-graduate students in writing.